SOCIO-CULTURAL IMPLICATION OF BALINESE WOMEN WORKING ON CRUISE SHIP - Oka, I Made Darma; Antara, Made; Mudana, I Gede (E-Journal of Cultural Studies, 2015)
The Balinese people tend to work on the cruise ship. In the last four years, the number of the Balinese women who work on the cruise ship has increased significantly, namely, by 33,84%. This present study is intended to analyze the socio-cultural implication of the Balinese women who work on the cruise ship as part of the tourism industry. Qualitative data are used in the present study. The data were analyzed qualitatively. The result of the study shows that the Balinese people were proud of being employed on the cruise ship as they had the opportunity to see the other countries which they had never dreamed of visiting. The socio-cultural life of the countries they had visited was unique and was completely different from the Balinese socio-cultural system. The socio-cultural life of the Balinese women who were employed on the cruise ship can be divided into; (a) the social implication; being employed on the cruise ship enabled them to improve the social status of themselves and their families, and (b) the cultural implication; being employed on the cruise ship enabled them to understand and conserve their culture. They acknowledged that their strong cultural tradition could impede them from being employed on the cruise ship. The paternal traditional life which is attached to the Balinese people and benefits the Balinese people sometimes cause the Balinese people to hesitate to be employed on the cruise ship.